The dynamics and the competitiveness of the metal furniture sector in the "Distrito" of Aveiro - Ana Isabel Melo; Elizabeth Brito (European Regional Science Association (ERSA), 2004)
In a context of globalization, competitiveness plays a prevailing role in the national, regional and local development, and depends progressively on companies' dynamics. In order to overcome an increasingly aggressive competition, companies must anticipate the consumers' preferences, rely on more innovative, first-rate products and know both their internal and external markets extremely well. In what concerns the metal furniture sector, new companies have been emerging and the existing ones have been expanding over the last few years in the “Distrito” of Aveiro. This sector has revealed a considerable competitive behaviour by creating job opportunities in this region and essentially by showing creativity and the will to innovate. Moreover, these companies are reaching international markets. Thus, the purpose of this study is to analyse the dynamics and competitiveness of this sector.
Keywords: 330